How would you solve the trigonometric identity (cosx-sinx)/(cosx+sinx)=sec2x-tan2x?

1 answer

sec 2x = 1/cos2x = 1/(cos^2x - sin^2x)
tan 2x = sin 2x / cos 2x = sin 2x / (cos^2 x - sin^2 x)
so
sec 2x -tan 2x = (1 - sin 2x) / (cos^2 x - sin^2 x)
= (1 - 2 sin x cos x) / (cos^2 x - sin^2 x)
= (1 - 2 sin x cos x)/ [(cos x - sin x)(cos x + sin x) ]
=====================================
now the left side
(cos x - sin x)(cos x - sin x) / [ cos x + sin x)(cos x - sin x)]
(cos^2 x - 2 sin x cos x + sin^2 x) / [ cos x + sin x)(cos x - sin x)]
(1 - 2 sin x cos x) / [ cos x + sin x)(cos x - sin x)]
remarkable, same as the right side
Similar Questions
  1. PLEASEE HELPPMEEE!!!!cot2x+sec2x=tan2x+csc2x and 1+2sinxcosx/sinx+cosx=sinx + cosx
    1. answers icon 1 answer
  2. (sinx - cosx)(sinx + cosx) = 2sin^2x -1I need some tips on trigonometric identities. Why shouldn't I just turn (sinx + cosx)
    1. answers icon 2 answers
  3. Simplify #3:[cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] =
    1. answers icon 1 answer
  4. Prove:tan2x+sec2x = cosx+sinx/ cosx-sinx
    1. answers icon 3 answers
more similar questions